2015
DOI: 10.1088/0953-4075/48/17/174005
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen molecular cation as a molecular antenna

Abstract: We study how the molecular hydrogen cation reacts to strong nonresonant fields, creating dipoles that oscillate at the driving carrier frequency. These dipoles are analogs of molecular antennas. The results are obtained by solving the time-dependent Schrödinger equation with simplified Hamiltonian models, assuming molecular orientation. Starting from the ground electronic state, we show under what conditions an optical molecular antenna is created and analyze its magnitude and the physical processes that lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…For lower frequencies the excursion length and the induced dipole could be larger, but tunneling ionization dominates. [99] In summary, we have shown that in order to create an oscillating electric dipole in a homonuclear diatomic cation without an oscillating driver one needs (i) to break the symmetry of the system and (ii) to sustain highly correlated electronic and nuclear motion, which are guaranteed by the LAMB dynamics.…”
Section: The Role Of the Electronic Chargementioning
confidence: 89%
See 4 more Smart Citations
“…For lower frequencies the excursion length and the induced dipole could be larger, but tunneling ionization dominates. [99] In summary, we have shown that in order to create an oscillating electric dipole in a homonuclear diatomic cation without an oscillating driver one needs (i) to break the symmetry of the system and (ii) to sustain highly correlated electronic and nuclear motion, which are guaranteed by the LAMB dynamics.…”
Section: The Role Of the Electronic Chargementioning
confidence: 89%
“…Here, we analyze the role of the electronic wave function and of electron-nuclear dynamics. [96,98,99] In a LAMB process, the total wave function of the system is a coherent superposition of both nuclear and electronic wave functions, [86] WðR; q; tÞ5/ g ðR; tÞN g ðq; RÞ1/ e ðR; tÞN e ðq; RÞ…”
Section: The Role Of the Electronic Chargementioning
confidence: 99%
See 3 more Smart Citations